1979
DOI: 10.1099/00221287-113-1-73
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plasmids from Antibiotic-resistant Shigella Isolates by Agarose Gel Electrophoresis

Abstract: ~ ~~ ~~Gel electrophoresis of DNA from 95 clinical isolates of Shigella sonnei and Shigella JIexneri resistant to antibiotics revealed a heterogeneous plasmid population. Most of the plasmids were smaller than 6 megadaltons (Mdal). Six S. sonnei isolates with the most common antibiotic resistance pattern were characterized. They had two plasmids in common : one was a self-transmissible Fif plasmid of 46 Mdal encoding tetracycline resistance, while the other was a 5.5 Mdal non-conjugative plasmid encoding resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…However, previously published reports revealed a heterogeneous plasmid population in strains of S. flexneri, with most plasmids being smaller than 6 MDa (17,42). A correlation between serotype and plasmid pattern was described in a previous report, in which it was suggested that the plasmid profile might be useful in the identification of epidemic clones of S. flexneri as they are introduced in a population (24).…”
Section: Resultsmentioning
confidence: 84%
“…However, previously published reports revealed a heterogeneous plasmid population in strains of S. flexneri, with most plasmids being smaller than 6 MDa (17,42). A correlation between serotype and plasmid pattern was described in a previous report, in which it was suggested that the plasmid profile might be useful in the identification of epidemic clones of S. flexneri as they are introduced in a population (24).…”
Section: Resultsmentioning
confidence: 84%
“…Shigellae usually harbour various plasmids, such as those required for bacterial invasion into the host intestinal epithelial cells and antibiotic resistance [17]. As many as 10 plasmids were contained in one strain [18]. Thus, plasmid profile analysis is one of the appropriate methods for molecular characterization of shigellae, while the technique is less useful for the bacteria that have only a few or no plasmids, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Results conformed with the data reported elsewhere that Shigella spp. harbours heterogeneous population of plasmids [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility also exists that these genes reside on a mobile genetic element acquired from another source. The finding that a region of DNA homologous to msgA exists on one of several cryptic plasmids known to exist in Shigella species (20) suggests a possible role of extrachromosomal elements in the mode of transfer of this region.…”
Section: Discussionmentioning
confidence: 99%